A biologically inspired fluid model of the cyclic service system - Kantarbayeva, Aliya; Mustafin, Almaz (Mathematical modelling and analysis, 2020)
A deterministic ﬂuid model in the form of nonlinear ordinary diﬀerential equations is developed to provide the description for a multichannel service system with service-in-random-order queue discipline, abandonment and re-entry, where servers are treated like enzyme molecules. The parametric analysis of the model’s ﬁxed point is given, particularly, how the arrival rate of new customers aﬀects the steady-state demand. It is also shown that the model implies a saturating clearing function (yield vs. demand) of the Karmarkar type providing the mean service time is much shorter than the characteristic waiting time.